Letter (translation)(copy)
1939-09-29 025a-0077-003 Copy. TRANSLATION. To the Administration of the Union of English Seaman, LONDON. Esteemed friends, We have received information of the call whioh the Government of the United Kingdom had made to the reservists of the war Fleets, and note that they have to rejoin before the 9th of the present month of August (?). We Spanish sailors who have taken refuge in the concentration camps of France address ourselves to you and offer our services in the Mercantile Marine of Great Britain to fill the gaps caused by the above mentioned call to service. We hope for your sympathetic consideration of the offer we are honoured to make: that is, we offer our services unconditionally in the hope of being useful to England to its Marine and to the struggle against Fascism in which all conscientious workers are obliged to take part in a greater or smaller degrees. To-day it is the English Government which [mobilises] the workers of the Mercantile Marine in order [to ... ] Navy. Very well then; to this call we call we respond, and we inform you and the English workers that we are present & ready without conditions. Signed on behalf of the Spanish sailors in the concentration camps. (6 signatures). Islote A., Barraca 12, Barcares, France. 292/946/25a/77(iii)